2005
DOI: 10.1111/j.1542-4758.2005.01153.x
|View full text |Cite
|
Sign up to set email alerts
|

The morbidity and cost implications of hemodialysis clinical performance measures

Abstract: Clinical performance measures, including dialysis dose, hemoglobin, albumin, and vascular access, are the focus of monitoring and quality improvement activities. However, little is known about the implications of clinical performance measures for hospital utilization and health care costs. We obtained clinical performance measures and hospitalization records for a national random sample of 10,650 hemodialysis patients and analyzed the relationship between changes in clinical performance measures and hospital u… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
10
0

Year Published

2006
2006
2014
2014

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(11 citation statements)
references
References 52 publications
(46 reference statements)
1
10
0
Order By: Relevance
“…This national longitudinal study shows that attainment of each of the individual targets is strongly associated with better outcomes, including decreased mortality, fewer hospitalizations, fewer days in the hospital, and lower overall Medicare hospital payments, validating the professional clinical practice guidelines [4]. A few studies of prevalent hemodialysis patients have shown associations of clinical performance target attainment with decreased hospital admissions and related costs [37,38], but this study adds to our knowledge of the effect of clinical performance target attainment in incident hemodialysis patients. Importantly, our results also provide new evidence that each additional target attained results in incremental improvement in these outcomes, regardless of which targets are attained, and provide a comprehensive examination of a variety of performance measures and outcomes.…”
Section: Discussionmentioning
confidence: 74%
See 1 more Smart Citation
“…This national longitudinal study shows that attainment of each of the individual targets is strongly associated with better outcomes, including decreased mortality, fewer hospitalizations, fewer days in the hospital, and lower overall Medicare hospital payments, validating the professional clinical practice guidelines [4]. A few studies of prevalent hemodialysis patients have shown associations of clinical performance target attainment with decreased hospital admissions and related costs [37,38], but this study adds to our knowledge of the effect of clinical performance target attainment in incident hemodialysis patients. Importantly, our results also provide new evidence that each additional target attained results in incremental improvement in these outcomes, regardless of which targets are attained, and provide a comprehensive examination of a variety of performance measures and outcomes.…”
Section: Discussionmentioning
confidence: 74%
“…However, whether attainment of accepted clinical performance targets for nutrition, bone disease management, anemia management, dialysis adequacy, and vascular access placement by hemodialysis patients have led to fewer hospitalizations, fewer hospital days, or decreased hospitalization costs, in addition to better patient survival, has been less well-studied [23,24]. In addition, the attainment of multiple clinical performance targets may or may not confer greater protection than the attainment of any single target.…”
Section: Introductionmentioning
confidence: 99%
“…For hospitalization outcomes in particular, a study by Metcalfe, Khan, Prescott, Simpson, and Macleod (2003) on 526 hemodialysis patients showed that 77% of them required hospitalization during the first year of renal replacement therapy, with a median of 13 hospitalization days for each patient. This is a worrying trend, as hospitalization is the major component of the cost of care of patients on dialysis (O'Connor, Wish, & Sehgal, 2005;St. Peter, Khan, & Ebben, 2004).…”
Section: Introductionmentioning
confidence: 99%
“…Abundant observational data support arteriovenous fistulas (fistulas) as the gold standard for vascular access in hemodialysis (HD) patients due to their optimal outcomes, such as better survival and lower cost (1)(2)(3). In contrast, central venous catheters (catheters), often placed for urgent dialysis or when a fistula has failed to mature, have been associated with increased risk of hospitalization (4) and death (5)(6)(7).…”
mentioning
confidence: 99%